Structural Disruption of Cilia and Increased Cytoplasmic Tubulin in Biliary Atresia—An Exploratory Study Focusing on Early Postoperative Prognosis Following Portoenterostomy - Patrícia Quelhas; Rui Oliveira; Carlos Kieling; Sandra Vieira; Jorge dos Santos (Biomedicines)
Introduction: Biliary atresia (BA) is a progressive hepatobiliary disease in infants, leading to liver failure and the need for transplantation. While its etiopathogenesis remains unclear, recent studies suggest primary cilia (PC) disruption plays a role. This study investigates correlations between PC and cytoplasmic tubulin (TUBA4A) alterations with hypoxia in patients with the isolated form of BA, focusing on native liver survival. Methods: Using qualitative and quantitative digital image analysis of immunofluorescence-stained liver samples, we assessed PC and TUBA4A features correlating these findings with HIF-1α nuclear positivity, clinical–laboratory data, and early native liver survival. Liver samples from fourteen BA patients and six controls with another liver disease were analyzed by digital image analysis, with data evaluated using Spearman’s correlation and independent t-tests. Results: HIF-1α positivity in cholangiocytes was observed in 42.8% of BA patients. While the PC ratio per biliary structure (cilia ratio status, CRs) was similar between BA patients and controls, PC length was decreased in BA patients. Cytoplasmic TUBA4A levels were elevated in BA patients. CRs positively correlated with lower cytoplasmic TUBA4A expression and was higher in patients without HIF-1α nuclear positivity. Reduced cilia length correlated with higher bilirubin levels at portoenterostomy. Predictors of early poor prognosis (death or need for transplantation until 1 year of life) included HIF-1α positivity, elevated direct bilirubin levels, decreased cilia length, PC bending, and increased TUBA4A expression. Conclusions: Reduced PC length, PC bending, and increased intensity of cytoplasmic TUBA4A expression occur in the isolated BA clinical type and negatively impact the early prognosis after post-portoenterostomy. These findings suggest the existence of a disruption in the tubulin transport between cytoplasm and PC. The detrimental effect of HIF-1alpha pathway activation over early native liver survival was confirmed, although independently from PC or cytoplasmic tubulin features.